Constructing identities a phenomenological exploration of Filipino childfree women’s lived experiences and social media practices. - Caspe, Kizia Gayle B.; Regala, Diana B.; Solis, Randy Jay C. (Quezon City College of Mass Communication, University of the Philippines, 2023)
Women in third-world countries begin to add voices to discourses on the traditional construction of the female identity. Previous studies cited new media as key sites for feminist discussions among women, including child freedom. However, little is known about this phenomenon in the Philippines. This thesis employed the Media Practice Model in the context of social media, as well as Feminist Poststructuralism, to understand Filipino women's childfree identity construction process and the prevailing discourses surrounding femininity in the Philippines. Interviews were conducted among 15 Filipino childfree women aged between 21 to 37 years old. For data triangulation. digital ethnography was implemented to observe their social media posts. Findings show that some Filipino women identified as childfree at an early age, while others have gone through a long decision process instead of a singular event influencing their decision. However, the terms childfree and childfreedom were first encountered through incidental consumption of social media content. These contents related to childfreedom further strengthened the decision to be childfree. Resistance to hegemonic discourses of modesty, marriage, and motherhood manifested in online and offline contexts. Counter-hegemonic discourses were created to redefine the Filipino woman. Practical recommendations to address the concerns of Filipino childfree women are discussed.
Vita.
Thesis
Includes bibliographical references (pages 178-204) and appendices (pages 205-214).
Keywords: Social media—Influence.; Childfree choice; Women and mass media